2011
DOI: 10.1111/j.1479-828x.2011.01323.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the feasibility of bilateral salpingo-oophorectomy during vaginal hysterectomy for uterine prolapse

Abstract: The feasibility of BSO was primarily dependent on the stage of pelvic organ prolapse and patients' age. Relaxation of the adnexae because of weakness of the infundibulo-pelvic ligaments may accompany severe pelvic organ prolapse and may potentially explain the feasibility of BSO in these women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
10
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 11 publications
2
10
1
Order By: Relevance
“…As a consequence, the findings should be applied to the general population with caution. Nonetheless, the age, parity, and levels of comorbidity among the patients included in the present analysis were comparable to those of other studies of transvaginal BSO . All procedures performed in the present study were for benign indications.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…As a consequence, the findings should be applied to the general population with caution. Nonetheless, the age, parity, and levels of comorbidity among the patients included in the present analysis were comparable to those of other studies of transvaginal BSO . All procedures performed in the present study were for benign indications.…”
Section: Discussionsupporting
confidence: 84%
“…When compared with vaginal hysterectomy alone, the use of transvaginal BSO plus vaginal hysterectomy increases the operative time by an average of 11-22 minutes, with no difference in length of hospital stay or adverse event rates. 14,15 Retrospective studies comparing these two approaches have also found transvaginal BSO plus vaginal hysterectomy to be as feasible and safe as vaginal hysterectomy alone. 23 Adverse event rates recorded in the present study for transvaginal BSO plus vaginal hysterectomy seemed broadly comparable to the reported adverse event rates for VH alone.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, some complications might have been related to a cuff abscess or bleeding from a pedicle unrelated to the salpingectomy. We chose to overestimate our possible complication rate as 3.8%; however this complication rate is what has been reported in the literature for hysterectomy only [12]. The pathological findings may have been underestimated, because they did not follow the standards for reporting [7].…”
Section: Discussionmentioning
confidence: 74%
“…Their series is not representative of Table 3 Complications for all procedures (n 5 425) our population or the general gynecology population, however. Dain and Abramov [12] similarly examined the success of surgery in women with advanced prolapse and identified degree of prolapse and age as significant factors for failure. We did not identify prolapse as a factor for success or failure of achieving salpingectomy.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation